PENERAPAN AFIRMASI POSITIF DALAM PRAKTIK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM OLEH GURU DI SEKOLAH - Salma Maelani Marwah; Agus Fakhruddin; Mokh. Iman Firmansyah (Mu'allim, 2026)
This study aims to deeply explore how Islamic Religious Education (PAI) teachers interpret and apply positive affirmations as an integral part of student character development. This study used a qualitative phenomenological approach, with data collected through in-depth interviews, participant observation, and document analysis. A thematic analysis of the experiences of nine PAI teachers revealed that positive affirmations are not merely motivational techniques, but rather a form of love, trust, and respect for children's potential, expressed through consistent and sincere words. The findings identified transformations in students' attitudes, strengthening of spiritual identity, and behavioral changes rooted in reflective, contextual affirmation practices supported by the teachers' social and emotional environment. The implications of this study emphasize the importance of integrating positive affirmations into a humanistic, spiritual, and sustainable educational strategy. Its contribution to national and global educational development is reflected in its support for SDGs Goal 4 (Quality Education) and SDG Goal 3 (Mental and Emotional Well-being), by transforming the classroom into an ecosystem for the holistic growth of children's character and spirituality. This research enriches the perspective of Islamic pedagogy and underscores the urgency of a humanizing affirmative approach.